Art as a Medium for Bilingualism and Biculturalism: Suggestions from the Research Literature (GIST – Education and Learning Research Journal, 2014)
This review of the literature critically explores the avenues to learning that visual art offers teachers and especially those with second language learners in their classrooms. The article is divided into seven sections in which the authors present research findings supporting the premise that learners’ cognitive processes are facilitated by images. Research cited strongly suggests visual art in instructional design helps students learn about world cultures, is an effective pre-writing activity, facilitates second language acquisition, and promotes biliteracy.
Keywords: cultures; second language acquisition; bilingual learners; multi-modal instruction